2021
DOI: 10.1021/acs.jpcc.1c05267
|View full text |Cite
|
Sign up to set email alerts
|

Monotonically Decreasing Ferromagnetic Resonance Linewidth of Cu/Ni0.81Fe0.19 Bilayer Heterostructures with the Increasing Sputtering Rate of the Cu Layer

Abstract: Permalloy with low ferromagnetic resonance linewidth has great application potential in spintronic/microwave devices. In this work, we demonstrated that the nonmagnetic (Cu) layer’s sputtering rate has a considerable impact on Ni0.81Fe0.19’s linewidth in Cu (4 nm)/Ni0.81Fe0.19 (3 nm) bilayer heterostructures. A monotonically decreasing out-of-plane linewidth was displayed as the sputtering rates increased from 0.27 to 1.75 Å/s due to interdiffusion. Meanwhile, a large reduction of the in-plane linewidth from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Compared to bare Py, the enhanced Δ H for bilayer manifests the evidence of spin current transport across the Py/(α + β)-W interface. Recent studies , suggest that suppressing TMS and surface magnetic anisotropy as a function of D r via interfacial engineering reduces the extrinsic contributions to the Δ H . In this study, we have obtained negligible extrinsic contributions without any interfacial layer as a function of D r .…”
Section: Resultsmentioning
confidence: 99%
“…Compared to bare Py, the enhanced Δ H for bilayer manifests the evidence of spin current transport across the Py/(α + β)-W interface. Recent studies , suggest that suppressing TMS and surface magnetic anisotropy as a function of D r via interfacial engineering reduces the extrinsic contributions to the Δ H . In this study, we have obtained negligible extrinsic contributions without any interfacial layer as a function of D r .…”
Section: Resultsmentioning
confidence: 99%
“…The diffusion bonding improved the dispersion of brittle materials and could improve the bonding strength of materials. Li et al [45] indicated that the interfacial diffusion between nanoscale films of Cu and Ni 81 Fe 19 was the main reason for the interfacial inhomogeneity. The intermixing of Cu with adjacent materials has been recognised as the main physical factor of deterioration of magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Permalloy is an extremely important spintronic material [24,25] having useful properties like high spin density, high magnetic permeability and low magnetic damping [26,27]. On the other hand Ta is being widely explored in FM/HM bilayers due to its high spin-orbit coupling that allows efficient charge current to spin current conversion and vice-versa [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…where γ is the gyromagnetic ratio and α is the dimensionless Gilbert magnetic damping parameter. α can be determined from the FMR linewidth [16][17][18]26]. In case of FM/NM heterostructures α can have additional contributions from spin pumping and spin back flow.…”
Section: Introductionmentioning
confidence: 99%